Analisis Komoditi Unggulan Sektor Pertanian di Kabupaten Gayo Lues Provinsi Aceh - Muji Burrahmad; Edy Marsudi; Lukman Hakim (Hasanuddin University, 2021)
This research is intended to determine the leading commodities that have growth and competitiveness and have priority to be developed in the Gayo Lues Regency. The research was conducted using Location Quotient (LQ) analysis, Shift Share (SS) analysis and Priority Commodity Development Priority analysis. The object used is agricultural commodities with limited research space on commodity production in each agricultural sub-sector in Gayo Lues Regency and Aceh Province. The results of the study show that agricultural leading commodities are peanuts, corn, rice, pineapple, shallots, cayenne pepper, large chili, tomatoes, siam orange, tobacco, candlenut, lemongrass, ginger, sugar palm, patchouli, sugar cane, buffalo, sheep, goats, cattle and rice field fisheries. Main commodities that have fast growth are rice, cayenne pepper, large chili, tomatoes, pineapple, serehwangi, tobacco, ginger, patchouli, cattle, goats and sheep. While commodities that have good competitiveness are corn, peanuts, large chillies, shallots, tomatoes, cayenne pepper, candlenut, tobacco, sugar palm, beef, buffalo, goats and sheep. The leading commodities that are the first priority to be developed are tobacco, cayenne pepper, large chillies, tomatoes, sheep, goats and cows. The second priority is pineapple, serehwangi, ginger, patchouli, rice, candlenut, shallots, sugar palm, peanuts, corn and buffalo. The third or alternative priority is rice fisheries, sugar cane and Siamese oranges.